2014
DOI: 10.7287/peerj.preprints.263v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extraordinary incidence of cervical ribs indicates vulnerable condition in Late Pleistocene mammoths

Abstract: The number of cervical vertebrae in mammals is highly conserved at seven. We have shown that changes of this number are selected against due to a coupling with major congenital abnormalities (pleiotropic effects, (Galis 1999, Galis et al. 2006, Varela-Lasheras et al. 2011, ten Broek et al. 2012). Here we show that the incidence of abnormal cervical vertebral numbers in Late Pleistocene mammoths from the North Sea is high (33.3%) and approximately 10 times higher than that of extant elephants (3.6%). Abnormal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…33% in mammoths before extinction (Reumer et al. ), 11% in minipigs (Kd, ) or 7.5% in humans (Palma & Carini, )]. Pedigrees were not available for analysis in any of the dogs included in this study; and therefore, the mode of inheritance or the degree of inbreeding could not be studied.…”
Section: Discussionmentioning
confidence: 99%
“…33% in mammoths before extinction (Reumer et al. ), 11% in minipigs (Kd, ) or 7.5% in humans (Palma & Carini, )]. Pedigrees were not available for analysis in any of the dogs included in this study; and therefore, the mode of inheritance or the degree of inbreeding could not be studied.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is further supported by the higher prevalence of cervical ribs in individuals with adverse outcomes. Several studies showed a high frequency of (rudimentary) cervical ribs in specific study populations [8], such as stillbirths and deceased neonates with and without structural anomalies [4], children suffering from malignancies [9] and extinct mammoths [10].…”
Section: Introductionmentioning
confidence: 99%